Pelatihan Pembuatan Pupuk Hayati di Desa Gondel, Kecamatan Kedungtuban, Kabupaten Blora, Jawa Tengah - Istikorini, Yunik; Firmansyah, Muhammad Alam; Kurniawati, Fitrianingrum; Mubin, Nadzirum (Institut Pertanian Bogor, 2024)
The rice productivity in Gondel Village, Kedungtuban District, Blora Regency, Central Java, has declined. Factors such as attacks by plant pests and diseases (OPT), climate change (DPI) impact, and decreasing soil quality are the leading causes of crop failure. This training aims to enhance the understanding and skills of Gondel Village farmers in making biofertilizers and introducing environmentally friendly pest and disease control methods. The activity involved 40 farmers from 8 farmer groups (Gemah Ripah, Margo Mulyo, Ngudi Makmur, Sido Dadi, Sido Makmur, Tambah Makmur, Tambah Rizki, and Sri Mulyo), with each group represented by five farmers. The training methods included analysis of soil chemicals, socialization, practical propagation of Trichoderma sp. on rice media, and biofertilizer production. Pre-test and post-tests were conducted to assess the improvement in farmers' knowledge. Trichoderma biofertilizer was formulated using carriers such as a) Manure and b) Compost, zeolite, and humic acid. The results of the soil chemical properties analysis showed that farmers' use of chemical fertilizers was very intensive, resulting in very high levels of phosphorus (P) and calcium (Ca) and high levels of potassium (K), magnesium (Mg), and cation exchange capacity (KTK). Evaluation results indicated that the training significantly improved the farmers' knowledge of biofertilizer production in theory and practice. However, some farmers still need further guidance on the propagation of the biological agent Trichoderma sp.